Influence of the Madden-Julian Oscillation on East African rainfall. Part I: Intraseasonal variability and regional dependency - (:unkn) unknown (My University, 2006)
The influence of the Madden-Julian Oscillation (MJO) on rainfall amounts over Equatorial East Africa (Kenya and northern Tanzania) is analysed for the period 1979-95 at the intraseasonal (pentad) time-scale. The two rainy seasons (March to May and October to December) are considered. Intraseasonal wet events in East Africa are embedded in large-scale zonal circulation anomaly patterns along the equator, showing distinct eastward propagation. It is further found that these wet events display a clear phasing with respect to the MJO cycle. This phasing is expressed as out-of-phase variations between the Highland and the coastal areas. Such a pattern is suggested to reflect different rain-causing mechanisms. MJO phases leading to wet spells in the western (Highland) region are those associated with the development of large-scale convection in the Africa/Indian Ocean region. These events are unambiguously related to deep convection, fuelled by low-level westerly moisture advection. MJO phases leading to wet spells in the eastern (coastal) region are often those associated with overall suppressed deep convection in the Africa/Indian Ocean region. However, these phases induce moisture advection from Indian Ocean. The possible role of stratiform rainfall or relatively shallow convection in the coastal wet spells observed in this phase is discussed. The contrasting rainfall conditions found in the two regions for the two opposite MJO phases are strongly correlated with the pressure gradient between the Indian and Atlantic Oceans.
Keywords: African Research